2017
DOI: 10.3390/v9010020
|View full text |Cite
|
Sign up to set email alerts
|

Envelope Protein Mutations L107F and E138K Are Important for Neurovirulence Attenuation for Japanese Encephalitis Virus SA14-14-2 Strain

Abstract: The attenuated Japanese encephalitis virus (JEV) strain SA14-14-2 has been successfully utilized to prevent JEV infection; however, the attenuation determinants have not been fully elucidated. The envelope (E) protein of the attenuated JEV SA14-14-2 strain differs from that of the virulent parental SA14 strain at eight amino acid positions (E107, E138, E176, E177, E264, E279, E315, and E439). Here, we investigated the SA14-14-2-attenuation determinants by mutating E107, E138, E176, E177, and E279 in SA14-14-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
53
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 36 publications
1
53
1
Order By: Relevance
“…Currently, some articles have confirmed several significant amino acid residue mutations on E gene. For example, mutations at residues L107F, E138K, I176V, T177A, E244G, Q264H, K279M, A315V, S366A and K439R are essential and important for neurovirulence attenuation [ 52 ], especially L107F, E138K [ 53 ] and M279K [ 54 ]. Mutation at residue S123R increase pathogenicity [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, some articles have confirmed several significant amino acid residue mutations on E gene. For example, mutations at residues L107F, E138K, I176V, T177A, E244G, Q264H, K279M, A315V, S366A and K439R are essential and important for neurovirulence attenuation [ 52 ], especially L107F, E138K [ 53 ] and M279K [ 54 ]. Mutation at residue S123R increase pathogenicity [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The chimeric virus JEV SA14/SA14-14-2, which took the JEV wild-type SA14 as the backbone, and in which only the prM/E genes of the JEV SA14 were replaced with that of JEV vaccine strain SA14-14-2, was recovered from BHK21 cells, and there are 10 amino acids substitution in the E protein of the chimera (L107F, E138K, I176T, V177A, E244G, Q264H, K279M, A315V, K439R, and G447D). We speculated that the characteristics of chimera should be similar with the vaccine strain from previous studies [20, 31]. In order to identify this, the biological characteristics of JEV SA14/SA14-14-2 were identified with the plaque assay and growth curve.…”
Section: Discussionmentioning
confidence: 99%
“…53,[86][87][88] Further, revertant mutations at E107 and E138 of the E gene resulted in greater SA14-14-2 virulence. 89 With JEV, three substitutions in domain III 90 (305F → V, 326K → E, and 380R → T) showed that neither positions 380 (380T) nor 305 (305V) independently affected neuroinvasiveness, whereas residue 326 was found to be a critical determinant of YFV neuroinvasiveness. 91 The study also indicated that changes at position 303 may be important for YFV virulence.…”
Section: Mutations In the E Protein Genementioning
confidence: 99%